If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x-13=7(x+2)-4(x-7)4
We move all terms to the left:
3x-13-(7(x+2)-4(x-7)4)=0
We calculate terms in parentheses: -(7(x+2)-4(x-7)4), so:We get rid of parentheses
7(x+2)-4(x-7)4
We multiply parentheses
7x-16x+14+112
We add all the numbers together, and all the variables
-9x+126
Back to the equation:
-(-9x+126)
3x+9x-126-13=0
We add all the numbers together, and all the variables
12x-139=0
We move all terms containing x to the left, all other terms to the right
12x=139
x=139/12
x=11+7/12
| 9(n+4)=65 | | y=12/5+3 | | x11+1=3 | | 8x-10+2x=25+5x | | (n^2)-12n=-32 | | -1(1-x)=(2x-2) | | -1=p+1-2 | | 2x^2+48=120 | | 7x+1+5x+1=4 | | 35x+6=2x-8 | | 2z/7-6=14 | | -4/9(18x•36)=-18 | | (n^2)=56-n | | -3+3x+12=45 | | 2x+6=130+x | | (13x-1)=180 | | 5y-57=108 | | 4-3x=46 | | -2x(2x-4)=4x | | 1+5(6+8x)=-1(3-2x) | | -14=5(x-4)-4(-5+3x) | | 5y=12+3 | | (6x-20)=(6x-4)=180 | | -54=9n+6+n | | 0.4x0.2(50)=0.3(x+40) | | 7m–2+8=10+5m | | 7x+75=12 | | 5z-44=71 | | -(5x6)-x=-6-6x | | 5(2x+5)=-36+31 | | 8x4+12=0 | | 5(11x+11)=440 |